6. ANALISIS RELIABILITY CENTERED MAINTENANCE (RCM) KOMPONEN HYDRAULIC PUMP PN MPEV3-011-8UK2B PESAWAT CN 235 100M/220M/MPA MELALUI PROGRAM PERAWATAN DI SKADRON UDARA 27 PAPUA - Yoga Bimantara, Anrianus; Bhirawa, W. Tedja; Mandagie, Karel L. (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2023)
In realizing the optimization of the maintenance capability of the CN 235 100M/220M/MPA Air Squadron 27, it is necessary to take steps to overcome the existing problems, namely carryingout preflight checks before carrying out flight crew missions, in this case the crew carries out checks onall aircraft systems and one of them is hydraulic system. Therefore, analytical measures are needed todetermine the reliability of this PN: MPEV3-011-8UK2B hydraulic pump. The theory used in analyzingthis problem is the theory of maintenance, the theory of Reliability Centered Maintenance (RCM), thetheory of reliability, the concept of willingness, Component Replacement Interval with Total MinimumDowntime and Paretto Diagram. The results of this study are from the time interval data required tocarry out maintenance or maintenance on the Hydraulic Pump PN component: MPEV3-011-8UK2Bon the CN 235 100M/220M/MPA aircraft is 30 (thirty) days, it has shown that the reliability of thiscomponent is also depending on the flight hours of the aircraft and the operation of the HydraulicSystem that is not excessive. The replacement schedule is carried out by prioritizing components whosereliability values are predicted to experience an extreme decline and have also been diagnosed aseligible to be replaced. The condition of the Hydraulic Pump Components on the CN 235 100M/220M/MPA Aircraft which has been influenced by several factors that cause an extreme decrease in reliabilityvalues, the appropriate method used is component replacement.